Effect of Stunting on Cognitive Development of Children: A Systematic Literature Review - Rosni Lubis; Delmaifanis Delmaifanis; Rosita Syarifah; Ani Kusumastuti; Herlyssa Herlyssa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting is a critical global health issue, with Indonesia ranking third in Southeast Asia for prevalence. This study examines the impact of stunting on cognitive development, its determinants, and interventions in Low- and Middle-Income Countries (LMICs). A systematic review was conducted across ProQuest, Ebsco, PubMed, and SpringerLink for English peer-reviewed articles (2009–2019). Using the PICOS framework, the review focused on stunted children (0–16 years) in LMICs. After screening 157 records and performing quality appraisals, 13 high-quality studies (scores >8/12) were selected for qualitative synthesis. Findings across Africa, Asia, and South America show stunting prevalence between 15.6% and 41.4%. Stunting typically manifests in the first three years due to chronic malnutrition and infectious diseases. Key risk factors include low socioeconomic status and parental education. Stunted children scored significantly lower in memory, spatial ability, and attention compared to non-stunted peers. While some children achieving catch-up growth showed improved results, those who recovered often still lagged behind children who were never stunted. Evidence confirms a strong correlation between stunting and impaired cognitive development. Despite global data, there remains a significant research gap regarding this specific correlation in Indonesia over the last decade.